Compondo o coletivo das Startups em Pato Branco - PR: uma cartografia das controvérsias na rede sociotécnica Sudovalley - Garbin, Murilo Henrique (2022)
This research was carried out with the general objective of mapping the controversies in the sociotechnical network of the Community of Startups of the Innovation Ecosystem of Southwest Paraná (Sudovalley), nucleus of Pato Branco. To this end, the actants were accompanied for a period of 27 (twentyseven) months. The study was based on the reference of the ActorNetwork Theory, and its associated methodological contribution of Cartography of Controversies. The members of the collective were identified, both human (the entrepreneurs, the professionals of the area, the consultants, the teachers and the spokesmen of the Public Power, of diverse entities and of educational institutions), and nonhuman (the infrastructure of startups, of other companies, of SEBRAE, of the Technology Park and of the Incubator , the products, the devices Whatsapp, Internet, Instagram, the law in its written standards and coronavirus). Following the actors, it was possible to identify and describe two controversies that mobilize the network: alleged betrayals to the goals of network insertion, culminating in forced attempt to close it in black box; and attractiveness, qualification and pricing of labor, defined as the "good controversy", because it's open and mobilizing the network. Identified the spokespersons who constituted the controversies and, therefore, the network itself, then, they were followed by conducting interviews and observations. The elaborated descriptions reinforced the perception that we are sociotechnical beings, highlighting the relationship between humans and nonhumans and the movements in network, which sometimes unfold from global to local, while other times from local to global, in a collective process of innovation construction, although it is sometimes taken by spokespeople in perspectives that are based on individual creativity and the centrality of the individual creator. Finally, the process of modernising, inserted in the network by multiple perspectives, tends to maintain the harmful socioenvironmental consequences, in particular the exploitation of humans and nature, which maintains unsustainable production paradigms, making it urgent that we come down to Earth and land somewhere.